Archived Geography - Rodríguez Coya, Fatima; Hernández Olivera, Luis M. (Tábula, 2024)
Presentation of “The power of place: the archival records of spaces and territories”, which aims to offer a comprehensive and updated perspective on the importance and impact of geographic documentation in archives. This monographic issue of Tábula provides a comprehensive look at fundamental topics such as the use of geospatial data and the application of new technologies, the management and organization of geographic documentation in archives, the documentary sources and geographic information stored in archives, and the relevance of toponymy in landscape understanding. By reading these articles professionals, academics, or simply those interested in geography will be able to immerse themselves in a fascinating journey through the records of spaces and territories and to gain greater knowledge and understanding of our environment, its evolution over time, and how all of this has been documented.